Cost-effectiveness analysis of pneumococcal vaccination for infants in China. Issue 50 (7th December 2016) - Maurer, Kristin A.; Chen, Huey-Fen; Wagner, Abram L.; Hegde, Sonia T.; Patel, Tejasi; Boulton, Matthew L.; Hutton, David W.
Highlights: China does not have a publicly funded pneumococcal vaccination program for infants. We evaluated the cost-effectiveness of adding PCV-7, PCV-10 and PCV-13 to the EPI. From the societal perspective, all vaccination programs are cost-effective. A PCV-13 program is most cost-effective and should be implemented in China. Abstract: Background: Although China has a high burden of pneumococcal disease among young children, the government does not administer publicly-funded pneumococcal conjugate vaccines (PCV) through its Expanded Program on Immunization (EPI). We evaluated the cost-effectiveness of publicly-funded PCV-7, PCV-10, and PCV-13 vaccination programs for infants in China. Methods: Using a Markov model, we simulated a cohort of 16 million Chinese infants to estimate the impact of PCV-7, PCV-10, and PCV-13 vaccination programs from a societal perspective. We extrapolated health states to estimate the effects of the programs over the course of a lifetime of 75 years. Parameters in the model were derived from a review of the literature. Results: We found that PCV-7, PCV-10, and PCV-13 vaccination programs would be cost-effective compared to no vaccination. However, PCV-13 had the lowest incremental cost-effectiveness ratio ($11, 464/QALY vs $16, 664/QALY for PCV-10 and $18, 224/QALY for PCV-7) due to a reduction in overall costs. Our sensitivity analysis revealed that the incremental cost-effectiveness ratios were most sensitive to the utility of acute otitis media, the cost of PCV-13, and the incidence of pneumonia and acute otitis media. Conclusions: The Chinese government should take steps to reduce the burden of pneumococcal diseases among young children through the inclusion of a pneumococcal conjugate vaccine in its EPI. Although all vaccinations would be cost-effective, PCV-13 would save more costs to the healthcare system and would be the preferred strategy.